Poetry as an Afro-Pacific Memory Stand in Los Versos de la Margarita, by Margarita Hurtado Castillo - Vivas, Julián; Amim, Valeria (Universidad Pedagógica y Tecnológica de Colombia, 2021)
Margarita Hurtado Castillo (1917-1992) was a great resonance box, receiver and transmitter of the sounds trapped in the eddies of marine time: she released them in poems, couplets or by telling stories like big fishing nets. This qualitative research, from a bibliographic nature, aims to characterize, from a decolonial perspective, aspects of the collective memory of the black Colombian Pacific’s communities showed in selected poems from Los Versos de la Margarita, a posthumous book by the oral narrator. It is intended to show that, in addition to compiling a past that in verse form exposes what it means to belong to this culture, Hurtado’s Oral Literature compositions act as discourses of resistance that promote collective consciences, exalt their ethnic identity and help to trace paths of emancipation from the macrostructures of our western world system of colonial, racist and patriarchal matrix.